CMS upgrade and future plans - Hoepfner Kerstin (EPJ Web of Conferences, 2015)
CMS plans for operation at the LHC phase-II unprecedented in terms of luminosity thus resulting in serious consequences for detector performance. To achieve the goal to maintain the present excellent performance of the CMS detector, several upgrades are necessary. To handle the high phase-II data rates, the readout and trigger systems are redesigned using recent technology developments. The high particle rates will accelerate detector aging and require replacement of the tracker and forward calorimeters. In addition, the muon system will be extended.